مدى جاهزیة المکتبات العامة المصریة للتصدى للازمات و للکوارث - د. محمد سعید محمد سعید (المجلة الدولية لعلوم المكتبات والمعلومات)
The purpose of this study is to identify the extent of policies, plans toconfront crises and disasters in Egyptian public libraries, to monitor the forms ofcrises, disasters that have actually occurred in Egyptian public libraries, and toanalyze the procedures in Egyptian public libraries, which ensure prevention andresponse to crises and disasters. On the reality of the training of specialists inEgyptian public libraries, which is being studied in the face of crises anddisasters. It also aims to identify the proposals of the directors of public librariesin Egypt to support methods of prevention, One of the most important findings ofthe study is that more than half of the public libraries under study have a writtenpolicy to deal with crises and disasters, but they are not comprehensive. One ofthe most important library proposals to support crisis and disaster prevention is toenhance the internal security of the library by placing iron on windows and doors,The purchase of robbery detection devices, the functioning of a virtual evacuationsimulation system and training in all forms of crisis.Results1. All the libraries in which there is a disaster and crisis management team.2. 95.45% of the public libraries under study The crisis and disaster teamconsists of the security officer and his staff.3. 54.54% of public libraries under study have a written policy for dealingwith crises and disasters, but they are not only library-specific and notcomprehensive.4. All public libraries in Egypt have a budget for disasters and crises and thisbudget is sufficient to some extent, but this budget is not independent, it isthe budget of the library.5. All the libraries under study have no insurance on their contents.6. The libraries under study were subjected to six types of crises: viruses,theft, deliberate sabotage, data spying, fire and electric diamonds.7. The libraries under study have succeeded in carrying out deterrentmeasures (fire, insects, rodents, pests, micro-disasters, administrativecrises, and health crises), while the procedures followed by libraries todeal with electronic crises, theft and vandalism are insufficient.8. The libraries in question have not taken any precautionary measuresagainst natural disasters and have not prepared them at all.